Is the German Mittelstand More Resistant to Crises? Empirical Evidence from the Great Recession - Michael Berlemann; Vera Jahn; Robert Lehmann (Center for Economic Studies and Ifo Institute (CESifo), 2020)
Germany's comparatively good economic performance throughout the Great Recession of the years 2008/2009 is often attributed to the business model of the German Mittelstand firm. Somewhat surprisingly, this claim has never been backed by empirical evidence. In this paper we use micro panel data from the ifo Business Survey to study the comparative performance of Mittelstand enterprises, defined as owner-managed SMEs. We present supporting evidence for the hypothesis that Mittelstand firms performed more stable throughout the Great Recession than non-Mittelstand firms. We also show that owner-managed SMEs performed significantly better than SMEs and owner-managed large enterprises. Thus, it is rather the combination of firm-size and owner-management that leads to more crisis resistance.
Keywords: E31; G12; 330; Mittelstand firms; Great Recession; crisis resistance